2018
DOI: 10.1590/abd1806-4841.20187031
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pyoderma gangrenosum as a predictor of hematological malignancies

Abstract: Pyoderma gangrenosum may precede, coexist or follow diverse systemic diseases. The bullous variety is usually associated with hematologic disorders. From 31 patients with pyoderma gangrenosum diagnosed in our hospital during 10 years, only 2 presented with the bullous type. One patient had previous diagnosis of chronic myeloid leukemia. Both had fast-progressive, painful lesions, and both showed an excellent response to systemic corticosteroids. In less than 3 months the lesions recurred simultaneously with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Other clinical subtypes of PG may be associated with underlying systemic diseases at different rates than classical PG. For example, it has been reported that 70% of Bullous PG cases develop alongside hematologic diseases, such as myelogenous leukemia, lymphoma, monoclonal gammopathy, and myelodysplastic syndromes [ 43 , 44 ].…”
Section: Pyoderma Gangrenosummentioning
confidence: 99%
See 1 more Smart Citation
“…Other clinical subtypes of PG may be associated with underlying systemic diseases at different rates than classical PG. For example, it has been reported that 70% of Bullous PG cases develop alongside hematologic diseases, such as myelogenous leukemia, lymphoma, monoclonal gammopathy, and myelodysplastic syndromes [ 43 , 44 ].…”
Section: Pyoderma Gangrenosummentioning
confidence: 99%
“…Evaluation should begin with a thorough medical history to the assessment of risk factors and associated diseases including the history of IBD, autoimmune arthritis, and/or malignancy. Temporal evaluation relating to underlying and triggering events should be considered, although initial PG diagnosis has been shown to both precede, coincide with, and/or follow underlying systemic disease activity [ 44 ].…”
Section: Pyoderma Gangrenosummentioning
confidence: 99%
“…In a systematic review published in 2015 including 823 cases of PG, HMs have been found to be associated with this condition in 12.5% of patients, following inflammatory bowel diseases ( n = 537; 65.2%) and polyarthritis ( n = 133; 16.1%) [ 66 ]. Haematological malignancies associated with PG, which are a major cause of death in this disease [ 41 , 67 ], are mainly represented by acute and chronic myeloid leukaemia [ 68 , 69 ], myelodysplastic syndrome [ 70 ], multiple myeloma [ 71 ], monoclonal gammopathy of undetermined significance [ 72 ] and lymphoma [ 73 ]. Although IgG isotype gammopathies are overall more frequent, most monoclonal gammopathies associated with PG are of the IgA isotype [ 47 , 74 ].…”
Section: Neutrophilic Dermatosesmentioning
confidence: 99%
“…IgG gammopathies are more frequent; however, the ones associated with PG are immunoglobulin A (IgA) [ 16 ]. The association between HM and PG has been observed as a cause of death [ 16 , 21 ], mainly in AML, CML, MDS, MM, MGUS, and lymphoma.…”
Section: Reviewmentioning
confidence: 99%